2021
DOI: 10.1007/s12035-021-02619-z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Long-Noncoding RNA LncZFAS1 Prevents MPP+-Induced Neuroinflammation Through MIB1 Activation

Abstract: Parkinson’s disease remains one of the leading neurodegenerative diseases in developed countries. Despite well-defined symptomology and pathology, the complexity of Parkinson’s disease prevents a full understanding of its etiological mechanism. Mechanistically, α-synuclein misfolding and aggregation appear to be central for disease progression, but mitochondrial dysfunction, dysfunctional protein clearance and ubiquitin/proteasome systems, and neuroinflammation have also been associated with Parkinson’s diseas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 79 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Damaged dopaminergic neurons can further activate NLRP3 in ammasome and pyroptosis, forming a vicious cycle [31] . TXNIP, as an upstream molecule of NLRP3 in ammasome, is positively correlated with NLRP3 [32] .Under disease or stress conditions, the levels of reactive oxygen species (ROS) in cells increase, leading to the separation of TXNIP from Trx1, thereby activating TXNIP. The activated TXNIP binds to NLRP3 protein, triggering the self-assembly of NLRP3, ASC and caspase 1, thereby forming the NLRP3 in ammasome complex [33] .The team used SH-SY5Y cell line to establish PD model in vitro, and found that LncRNA ZFAS1 was highly expressed in MPTP-induced PD cell model.…”
Section: Discussionmentioning
confidence: 99%
“…Damaged dopaminergic neurons can further activate NLRP3 in ammasome and pyroptosis, forming a vicious cycle [31] . TXNIP, as an upstream molecule of NLRP3 in ammasome, is positively correlated with NLRP3 [32] .Under disease or stress conditions, the levels of reactive oxygen species (ROS) in cells increase, leading to the separation of TXNIP from Trx1, thereby activating TXNIP. The activated TXNIP binds to NLRP3 protein, triggering the self-assembly of NLRP3, ASC and caspase 1, thereby forming the NLRP3 in ammasome complex [33] .The team used SH-SY5Y cell line to establish PD model in vitro, and found that LncRNA ZFAS1 was highly expressed in MPTP-induced PD cell model.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to pyroptosis, a study identified ZFAS1 as one of eight pyroptosis-related prognostic lncRNAs for oral squamous cell carcinoma using clinicopatholog-ical data, revealing its potential as part of a signature for patient risk stratification and predicting clinical outcomes including overall survival and tumor immune microenvironment [25]. Zhu et al [26] proved that ZFAS1 was a regulator of inflammasome activation and pyroptosis in human neuroblast SH-SY5Y cells following 1-methyl-4-phenylpyridinium (MPP + ) treatment that related with Parkinson's disease. Consistently, in the present study, we found that ZFAS1 was downregulated in allergic rhinitis, and overexpression of ZFAS1 significantly promoted cell viability and inhibited pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This altered expression inhibited mindbomb E3 Ub protein ligase 1 (MIB1) protein expression and directly interfered with the MIB1-dependent ubiquitination of thioredoxin interacting protein (TXNIP). As a result, NLPR3 inflammasomes were activated, promoting inflammatory response and pyroptosis in SH-SY5Y cells [ 65 ]. A loss of Parkin activity and overaccumulation of NLRP3 inflammasome was observed in the brain tissues of LPS-induced mouse models of Parkinson’s disease (PD).…”
Section: Nlrp3 Inflammasome Ubiquitination/deubiquitination and Infla...mentioning
confidence: 99%